(untitled) (Annals of Medical Research, 2021)
Aim: To determine the relationship between established prognostic markers and Ki67 proliferative index in breast cancer patients and investigate variations of prognostic parameters between material types (tru-cut biopsy or resection). Material and Methods: Breast cancer cases reported in our laboratory between July 2015 and December 2019, as well as estrogen receptor (ER), progesterone receptor (PR), CerbB2, Ki-67 staining results, tumor type, histologic grade, tumor size, lymph node metastasis status parameters were obtained from the automation system. Tru-cut biopsy and resection materials were evaluated and the parameters were compared. Results: 726 materials taken from 571 adult patients were included in this study. 297 (40.9%) of the cases were evaluated by tru-cut biopsy and 430 (59.1%) were resection material. The mean ER staining percentage was 86.5 (± 10.36) and it was 61.65 (± 22.84) for PR. Ki-67 proliferative index had an average value of 26.58 (± 17.67). There was no difference between the material types in terms of immunohistochemical markers, whereas there were differences between the two material types in histological grade results.Conclusion: Besides established immunohistochemical prognostic markers, Ki67 proliferative index should be utilized in breast cancer cases and determination of histological grade in tru-cut biopsies is valuable for the clinical management of the tumor.